2009
DOI: 10.1002/bem.20474
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional study of 12‐O‐tetradecanoyl‐13‐phorbol acetate (TPA)‐induced differentiation of U937 cells under exposure to a 6 mT static magnetic field

Abstract: This study deals with the morphofunctional influence of 72 h exposure to a 6 mT static magnetic field (SMF) during differentiation induced by 50 ng/ml 12-O-tetradecanoyl-13-phorbol acetate (TPA) in human leukaemia U937 cells. The cell morphology of U937 cells was investigated by optic and electron microscopy. Specific antibodies and/or molecules were used to label CD11c, CD14, phosphatidylserine, F-actin and to investigate the distribution and activity of lysosomes, mitochondria and SER. [Ca(2+)](i) was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
(78 reference statements)
2
20
0
1
Order By: Relevance
“…For example, a 50 Hz, 1-50 mT, ELF-PMF induces non-linear changes in both cell membrane conductivity and permittivity in in vitro-cultivated primary embryonic chicken myoblasts after 1 h of exposure; conversely, when the same cells are exposed for 1 h to a DC-induced SMF of 1, 3, or 5 mT, i.e., values comparable with those of the ELF-PMF used in the same study, no change in the same membrane electrical parameters was observed in comparison to control values [3,4]. MF exposure also induces variations in the inner mitochondrial transmembrane potential of differentiated U937 (6 mT, for up to 72 h) and SH-SY5Y cells (1.4 mT, 50 Hz, ELF-PMF, for up to 4 h) [16,17]. Interestingly, these experimental observations have been mathematically rationalized by Ye et al, (2010).…”
Section: Alteration Of Electrical Parameterssupporting
confidence: 60%
See 4 more Smart Citations
“…For example, a 50 Hz, 1-50 mT, ELF-PMF induces non-linear changes in both cell membrane conductivity and permittivity in in vitro-cultivated primary embryonic chicken myoblasts after 1 h of exposure; conversely, when the same cells are exposed for 1 h to a DC-induced SMF of 1, 3, or 5 mT, i.e., values comparable with those of the ELF-PMF used in the same study, no change in the same membrane electrical parameters was observed in comparison to control values [3,4]. MF exposure also induces variations in the inner mitochondrial transmembrane potential of differentiated U937 (6 mT, for up to 72 h) and SH-SY5Y cells (1.4 mT, 50 Hz, ELF-PMF, for up to 4 h) [16,17]. Interestingly, these experimental observations have been mathematically rationalized by Ye et al, (2010).…”
Section: Alteration Of Electrical Parameterssupporting
confidence: 60%
“…Therefore, the alterations induced by the MF exposure are the result of alterations affecting the cytoskeletal components (actin filaments, microtubules and intermediate filaments) which help the cells to maintain their shape and internal structures. In fact, a de-arrangement of the F-actin microfilaments, with their depolymerisation and marginalization from the centre towards the cell membrane, was found in differentiated U937, as well as in Raji or HaCaT cells exposed to a 6 mT SMF (for up to 72 h) or to a 2 mT, 50 Hz, ELF-EMF (for up to 72 or 96 h), respectively [16,19,31]. Dini et al, (2005 and found that some substances (i.e., 12-0-tetradecanoyl-13-phorbol acetate (TPA), low concentration of glutamine, dimethyl sulfoxide) induce U937 cell differentiation through a progressively lower degree.…”
Section: Incidence On Intracellular Calcium Concentrationmentioning
confidence: 98%
See 3 more Smart Citations